(untitled) (Annals of Medical Research, 2022)
Aim: Drug hypersensitivity is an important issue encountered by clinicians during clinical practice in Turkey and in the world. Any drug used for diagnosis or treatment has the potential to cause hypersensitivity reactions. The aim of the present study was to review the distribution of drugs reported to cause hypersensitivity reactions and to determine the distribution of tests and test results among patients that presented to the adult allergy and immunology outpatient clinic with immediate-type drug hypersensitivity in the Malatya province. Materials and Methods: The study included adult patients who were admitted with immediate-type drug hypersensitivity (allergic and/or non-allergic) between October 2017 and October 2020 and underwent testing for drugs. Age, sex, atopic diseases (asthma, allergic rhinitis, urticaria, eczema), culprit drug(s), drug reaction types, time of reaction onset, and skin and drug provocation test results were evaluated. Results: Of the 107 patients included, 83 (77.6%) were female and 24 (22.4%) were male. The mean age was 40.74 ± 11.28 years. There was a history of drug hypersensitivity to antibiotics in 44 patients (41.1%) and analgesics in 56 patients (52.3%). Urticaria and/or angioedema were the most common reactions to culprit drugs. Overall, 148 tests for drug hypersensitivity were performed, and the positivity rate was 6.1%. Conclusion: Analgesics and antibiotics were the most common causative agents in patients presenting to allergy outpatient clinics with drug allergy, and reactions occurred even with alternative agents. Thus, patients reporting drug reactions should undergo drug tests before physicians recommend drugs.